2021
DOI: 10.1029/2020gl092017
|View full text |Cite
|
Sign up to set email alerts
|

Major Differences in Regional Climate Impact Between High‐ and Low‐Latitude Volcanic Eruptions

Abstract: Volcanic eruptions impact the radiative balance of Earth's atmosphere due to scattering, absorption and reflection of radiation by volcanic aerosols. Explosive eruptions, where the volcanic plume reaches the stratosphere, have the strongest climate effect due to the volcanic aerosols preventing part of the radiation entering the troposphere, as well as the prolonged life time of stratospheric aerosols. The climate effects of large volcanic eruptions have been documented by observations. Most notably the 1991 P… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 33 publications
0
3
0
Order By: Relevance
“…It is possible, that the differences in changes of the tropopause depth offer an explanation for the findings of Sjolte et al (2021) that mid-and low latitude eruptions have differing impacts on the North Atlantic Oscillation. An objection could be, that the ETCs have an impact on the depth of the troposphere themselves, and hence they cannot explain changes in the ETC distribution.…”
Section: The Combined Thermal Pattern and The Location Of The Eruptionmentioning
confidence: 99%
See 1 more Smart Citation
“…It is possible, that the differences in changes of the tropopause depth offer an explanation for the findings of Sjolte et al (2021) that mid-and low latitude eruptions have differing impacts on the North Atlantic Oscillation. An objection could be, that the ETCs have an impact on the depth of the troposphere themselves, and hence they cannot explain changes in the ETC distribution.…”
Section: The Combined Thermal Pattern and The Location Of The Eruptionmentioning
confidence: 99%
“…Eruption impacts on stratospheric circulation have been studied intensely (Graft et al 1993, Bittner et al 2016, DallaSanta et al 2019. In contrast, the impact of eruptions on high and mid-latitude circulation and weather has so far mostly been quantified by analysing single site proxies (Dawson et al 2007, Kuijpers andMikkelsen 2009) or large-scale circulation indices such as the Atlantic Multidecadal Oscillation (Birkel et al 2018, Mann et al 2021, the North Atlantic Oscillation (Robock 2000, Sjolte et al 2021 or the Arctic Oscillation (Stenchikov et al 2002, Christiansen 2008. Although these indices do correlate with surface weather patterns (Laurila et al 2021), they express only temporally and spatially integrated information.…”
Section: Introductionmentioning
confidence: 99%
“…For high-latitude volcanic eruptions, Oman et al (2005) reported rather minor responses of Arctic polar vortex and unclear surface anomalies following the Katmai eruption which occurred at 58 • N. In contrast, Zambri et al (2019) showed negative NAO after the 1783 Laki eruption which occurred at 64 • N. Sjolte et al (2021) additionally presented the appearance of positive and negative NAO to low-and NH high-latitude volcanic eruptions, respectively, during the last millennium from climate reconstructions. In This result indicates that extratropical circulation and surface climate responses to volcanic eruptions are dependent on the latitude of volcanic eruptions.…”
Section: Uncertainties Of Climate Model Simulationsmentioning
confidence: 99%